2019
DOI: 10.5603/ep.a2019.0027
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of GWAS variants associated with differentiated thyroid cancer

Abstract: The genetic risk of differentiated thyroid cancer (DTC) probably consists of multiple low-penetrance, single-nucleotide polymorphisms (SNP). Such markers are difficult to uncover by linkage analysis but can be revealed by association studies. Genome-wide association studies (GWASs) have uncovered 31 SNPs associated with DTC. These markers carry a low to moderate risk for DTC, but their cumulative effect increases with each successive risk allele. These data support the important contribution of low penetrance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
(75 reference statements)
0
8
0
Order By: Relevance
“…may help stratify individuals according to their risk of developing DTC, which can be useful for elaborating screening policies. Moreover, inherited genetic factors can also impact the final outcome of the disease such as histological subtypes, localization of metastases, or molecular profiling of the tumor, and their characterization can help to predict effectiveness of the initial treatment [120].…”
Section: Discussionmentioning
confidence: 99%
“…may help stratify individuals according to their risk of developing DTC, which can be useful for elaborating screening policies. Moreover, inherited genetic factors can also impact the final outcome of the disease such as histological subtypes, localization of metastases, or molecular profiling of the tumor, and their characterization can help to predict effectiveness of the initial treatment [120].…”
Section: Discussionmentioning
confidence: 99%
“…Integration of the PRS with clinical factors was shown to improve the prediction of subsequent thyroid cancer in childhood cancer survivors 49 . Individual variants were tested for their association with tumor size, locoregional and distant metastases, extrathyroidal extension, and multifocality (reviewed in 50 ). We demonstrated that incorporating PRS into the thyroid nodule risk stratification results in an improved ability to discriminate between benign and malignant nodules as measured by the classifier AUROC (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggests that rs965513 is associated with tumours >10mm and multifocality. A recent review identifies rs965513 as being associated with increased DTC tumour size and extra-thyroidal extension ( Jendrzejewski et al 2019 ). Other germline mutations have also been linked to additional pathological characteristics including nodal disease burden, metastatic disease and disease-specific mortality ( Jendrzejewski et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%